Pengembangan “pHelper” Kalkulator pH Larutan Berbasis Web Sebagai Media Pembelajaran Kimia - Winoto, Sebastian Wilbert; Galih, Aileen Vitta Budiman; Awahita, Himeriko; Irmita, Luthfia Ulva (Chemistry Education Department of Education and Teaching Faculty, 2023)
In the 21st century and approaching the upcoming Industrial Revolution 5.0, advancements in science education are of paramount importance. Moreover, chemistry and science education in the upcoming Industrial Revolution 5.0 will heavily rely on technology. This research introduces